PENGARUH PRESTASI KERJA TERHADAP PROMOSI JABATAN PNS PADA KANTOR KECAMATAN PITUMPANUA KABUPATEN WAJO - Maspawati Tokang; Andi Supriadi (BADAN PENERBIT STIEPARI PRESS, 2023)
This research was conducted at the Pitumpanua District Office, Wajo Regency by raising the research problem about the Effect of Work Performance on the Promotion of Civil Servant Positions at the Pitumpanua District Office, Wajo Regency. The population in this study were all civil servants at the Pitumpanua District Office, Wajo Regency, totaling 17 people. This type of research is a census research type with a quantitative research approach, which intends to test the effect of the independent variable on the dependent variable, namely work performance on the promotion of civil servant positions at the Pitumpanua District Office, Wajo Regency.